2022
DOI: 10.3389/ijph.2022.1605021
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Incidence of Vulvar and Vaginal Cancers With Different Histology by Race, Age, and Region in the United States (2001–2018)

Abstract: Objectives: The race, age, and region-stratified incidence of vulvar (VUC) and vaginal (VAC) cancers with different histology were unclear.Methods: Data was retrieved from the United States Cancer Statistics database. Average annual percent change (AAPC) and incidence rate ratio (IRR) were calculated.Results: Overall, VUC incidence increased from 18.3 (per 1,000,000 woman-years) to 19.6, but VAC incidence decreased from 5.6 to 4.4. VUC squamous cell carcinoma (SCC) incidence increased (AAPC, 0.96; 95% CI, 0.66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 29 publications
2
17
1
Order By: Relevance
“…In the study from Japan between 2001 and 2010, the number of vulvar cancer cases increased in women ≥80 years of age from 18.0% to 30.6% ( P < 0.05) in Japanese women during the study period; this change was not seen in the US validation cohort (25.2% to 27.8%; P = 0.160) 30 . Another study from USA in 2001–2018 observed an increase in vulvar SCC in women aged 70–79 years of age at diagnosis, but no change for women ≥80 years of age 4 . The SQRGC study on vulvar SCC observed that fewer women ≥80 years of age did not receive any cancer treatment due, for example, to comorbidity, poor performance status or patients’ wish 28 .…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In the study from Japan between 2001 and 2010, the number of vulvar cancer cases increased in women ≥80 years of age from 18.0% to 30.6% ( P < 0.05) in Japanese women during the study period; this change was not seen in the US validation cohort (25.2% to 27.8%; P = 0.160) 30 . Another study from USA in 2001–2018 observed an increase in vulvar SCC in women aged 70–79 years of age at diagnosis, but no change for women ≥80 years of age 4 . The SQRGC study on vulvar SCC observed that fewer women ≥80 years of age did not receive any cancer treatment due, for example, to comorbidity, poor performance status or patients’ wish 28 .…”
Section: Discussionmentioning
confidence: 86%
“…29 This dis- ogies. 4 In a study from Japan between 2001 and 2010, SCC constituted 72.4% of cases, followed by Paget's disease (14.3%) and AC (5.6%). 30 During the study period a decrease in age-standardized incidence of MM of the vulva was found, whereas an increase in the age-standardized incidence of AC was observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While women with vulvar cancer are on average older at diagnosis, compared with other gynecologic cancers, we understand that other variables exist that may impact post-operative and oncologic outcomes and that many women are diagnosed at a younger age. For example, Black women may be diagnosed with vulvar cancer at an earlier age, with more advanced disease, and have significantly worse outcomes 32–34. Due to the relative rarity of vulvar cancer, there is limited research to support how specific medical comorbidities influence oncologic and surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%